Operando Fe dissolution in Fe-N-C electrocatalysts during acidic oxygen reduction: impact of local pH change - Pedersen, Angus; Kumar, Kavita; Ku, Yu Ping; Martin, Vincent; Dubau, Laetitia; Santos, Keyla Teixeira; Barrio, Jesús; Saveleva, Viktoriia A.; Glatzel, Pieter; Paidi, Vinod K.; Li, Xiaoyan; Hutzler, Andreas; et al. (Energy and Environmental Science, 2024)
Atomic Fe in N-doped C (Fe-N-C) catalysts provide the most promising non-precious metal O2 reduction activity at the cathodes of proton exchange membrane fuel cells. However, one of the biggest remaining challenges to address towards their implementation in fuel cells is their limited durability. Fe demetallation has been suggested as the primary initial degradation mechanism. However, the fate of Fe under different operating conditions varies. Here, we monitor operando Fe dissolution of a highly porous and >50% FeNx electrochemical utilization Fe-N-C catalyst in 0.1 M HClO4, under O2 and Ar at different temperatures, in both flow cell and gas diffusion electrode (GDE) half-cell coupled to inductively coupled plasma mass spectrometry (ICP-MS). By combining these results with pre- and post-mortem analyses, we demonstrate that in the absence of oxygen, Fe cations diffuse away within the liquid phase. Conversely, at −15 mA cm−2geo and more negative O2 reduction currents, the Fe cations reprecipitate as Fe-oxides. We support our conclusions with a microkinetic model, revealing that the local pH in the catalyst layer predominantly accounts for the observed trend. Even at a moderate O2 reduction current density of −15 mA cm−2geo at 25 °C, a significant H+ consumption and therefore pH increase (pH = 8-9) within the bulk Fe-N-C layer facilitate precipitation of Fe cations. This work provides a unified view on the Fe dissolution degradation mechanism for a model Fe-N-C in both high-throughput flow cell and practical operating GDE conditions, underscoring the crucial role of local pH in regulating the stability of the active sites.
CRIS-Team Scopus Importer:2024-08-16